12-Years Compulsory Education Policy and Education Participation Completeness:Evidence from Indonesia: Evidence from Indonesia - Cep Kiki Kusumah (Pusbindiklatren Bappenas, 2021)
Indonesia is facing a problem with education outcomes, both in access and quality. To increase education access and participation, the President of Indonesia committed to implementing a 12-years compulsory education policy. As a result, upper secondary education’s completion rate has increased significantly in districts that implement 12-years compulsory education rather than in districts that did not implement it. Strategies attached to the policy also considerably affect the completion rate, except for providing community learning centers. However, in every model, the implementation of 12-years compulsory education always significantly affects upper secondary education’s completion rate. The district government that implemented 12-years compulsory education has achieved this condition because of the innovative effort to reach this target.